Law Enforcement of Alcoholic Beverage Circulation in Cirebon Regency: A Study of Perda No.4/2021 Amendments to Perda No.7/2015 concerning Public Order - Octaviyana, Santy (Jurnal Legisci, 2023)
Social problems that occur in the community can disrupt existing order and security. Of the many problems faced by this country, one of them that is of particular concern to the government is the problem of liquor, which is still widely found and consumed by the public. In this Regional Regulation, the subjects are people and business entities that circulate alcoholic beverages. This study aims to determine law enforcement efforts and obstacles faced by law enforcement officials in the circulation of alcoholic beverages. This study aims to determine how law enforcement officials face law enforcement efforts and obstacles to the circulation of alcoholic beverages based on Cirebon Regency Perda Number 4/2021 Amendments to Perda Number 7/2015 concerning public order. The method used in this study is qualitative; from the study results, it can be concluded that law enforcement of the circulation of alcoholic beverages based on Perda Number 4/2021 Amendments to Regional Regulation Number 7/2015 concerning Public Order has not been maximized. This is evidenced by the large number of alcoholic beverage business actors who do not have business licenses and do not know that Cirebon Regency has a policy regarding public order.